The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015 IEEE International Conference on Industrial Technology (ICIT) 2015
DOI: 10.1109/icit.2015.7125594
|View full text |Cite
|
Sign up to set email alerts
|

Low cost microfluidic device for partial cell separation: Micromilling approach

Abstract: Several studies have already demonstrated that it is possible to perform blood flow studies in microfluidic systems fabricated by using low-cost techniques. However, most of these techniques do not produce microchannels smaller than 100 microns and as a result they have several limitations related to blood cell separation. Recently, manufacturers have been able to produce milling tools smaller than 100 microns, which consequently have promoted the ability of micromilling machines to fabricate microfluidic devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…A key attraction of microfluidics technology is that high precision devices can be rapidly fabricated at low cost. Although numerous fabrication methods exist [ 5 , 6 , 7 ], microfluidic chips are most easily fabricated by molding formable polymers, such as polydimethylsiloxane (PDMS), which are primarily fabricated for proof-of-concept microfluidic devices. To ensure correct operation on each fabricated device, microchannel geometry must be accurately imprinted from mold to polymer.…”
Section: Introductionmentioning
confidence: 99%
“…A key attraction of microfluidics technology is that high precision devices can be rapidly fabricated at low cost. Although numerous fabrication methods exist [ 5 , 6 , 7 ], microfluidic chips are most easily fabricated by molding formable polymers, such as polydimethylsiloxane (PDMS), which are primarily fabricated for proof-of-concept microfluidic devices. To ensure correct operation on each fabricated device, microchannel geometry must be accurately imprinted from mold to polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the heat resulting from the high rotation speed can damage the milling tool and the milled channels. After finishing the milling process and cleaning the device with water and detergent, the depth of the microchannels can be measured by means of a 3D optical profiler using confocal and interferometric principle (Sensofar, plu neox) [22].…”
Section: Fabrication Of the Microfluidic Devicementioning
confidence: 99%
“…Research has shown that the wall roughness and micro topography can significantly affect the flow and drag along the microfluidic channel path [11], and microreactors often need to control the flow pattern to achieve enhanced mixing, to achieve enhanced mass transfer, and improve the reaction rate. And on the other hand, design and control of wall roughness and micro topography has become an effective means of micro-flow control [12][13][14]. In addition, the micro features size produced by micro milling makes the subsequent finishing processes, e.g., grinding or polishing, expensive or even impossible.…”
Section: Introductionmentioning
confidence: 99%